Estrutura econômica, mercado de trabalho e evolução sócio-ocupacional no Rio Grande do Norte 2001 a 2008: reflexo de uma condição mercantil e estruturalmente periférica - Fernandes, Kaio César (2011)
The aim of this thesis was to investigate the evolution of the socio-occupational status in Rio Grande do Norte from 2001 to 2008, based on the characterization of the socio-economic status of this State from the analysis of labor market norte-rio-grandense . The study, specifically, drew a comparison between the dynamics of the labor market in Rio Grande do Norte and the capital city, Natal. From this perspective, the purpose was to make a relationship between the social division of labor and its effects on the socio-spatial division, represented in the "macro scale" by the federal unit and the "micro level" for the capital; locus of economic and population concentration. The collection of data on the labor market had as a major source PNAD/IBGE, characterizing the labor market in many ways: people of working age, economically active population and employed and unemployed people, classified by age, sex, color, education, income and social protection condition. However, as for the socio-occupational division, we follow the methodology used by the research group on national television, based in IPPUR /UFRJ, called Monitoring of the Metropolis," which rallied twenty-four groups that aggregate the occupations found in the PNAD/IBGE, in eight groups of socio-occupational categories, according to the similarity between them. It was used in the socio-spatial cutting two relevant discussions, which are inter-related and were characterized as crucial points in developing the research problem: the former was related to the influence of the hegemony of merchant capital in the labor market in Rio Grande North and, the latter, it referred the socio-economic relations between the territory and the variable occupation. Lastly, the results all indicated that in Rio Grande do Norte, as a peripheral state, has suffered the devastating influence of the hegemony of capital purely commercial basis, where "wealth" of capitalism is generated through the sphere of mere movement of goods and services rather than a productive process due to the social relations of production more advanced. We have a little advanced economic structure, with a tertiary sector that has propagated under-employment or disguised unemployment. Similarly, the agricultural sector has been presented as an example of greater social degradation of working conditions in the state. The secondary sector, in turn, also was not behind this uncertainty; on the contrary, confirmed that condition, with poor levels of income, low education of the workforce and a high degree of social helplessness, even in the state capital, space full urban area, which although always appear with a favorable condition compared to Province, in practically most of the variables studied, was also reflected at the same time the author of a structurally underdeveloped condition